Electrocatalytic Oxidation of Hydrogen Peroxide on the Graphite Electrode Based on Silver Nanoparticles; Key Engineering Materials; Vol. 743 : High Technology: Research and Applications (HTRA 2016) - Perevezentseva D. O. Dariya Olegovna; Gorchakov E. Eduard; Fedotova D. Daria; Bimatov V. Vladimir; Triphonova E. P. Evgenya Petrovna (2017, 2017)
Title screen